Promoting Learning from Home Environments Through Google Classroom Application for EFL Undergraduates - Amrina Rosyada (Deiksis, 2020)
As the world has been shocked by the unexpected rapid disease named COVID-19, several emergency actions are conducted in all aspects of human lives, including in the education field. In Indonesia, all colleges, particularly in several red-zone areas such as Jakarta, are restricted accessed for several months ahead. All activities inside the institutions’ building are limited, and face-to-face classrooms are forbidden and changed into virtual classrooms or called Learning from Home Environments (LHE). Regarding the situation, this research is promoting LHE with the use of Google Classroom application as a free available media in teaching English basic grammar course for EFL undergraduates. This research was participated by 60 students of English Education Program, Universitas Indraprasta PGRI (Unindra), located in Jakarta, Indonesia. The research administered a convergent mixed-method research design by collecting data in two cycles that accumulated through tests and questionnaires. Based on research questions, a correlational analysis and a narrative analysis were allocated. The results indicate an interesting output on students’ course engagement and course understanding. Supported by several practical and simple features, Google Classroom becomes a promising and favorite tool in learning English from home environments during the pandemic period.Keywords: Learning from home environments, google classroom application, EFL undergraduates, virtual classroom, pandemic period